(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
: This article, The Theory of Articles in Modern English, provides an in-depth exploration of the role and function of articles in English grammar. It categorizes articles into definite ("the"), indefinite ("a/an"), and zero article usage, explaining their application and importance in indicating definiteness, specificity, and countability. The article highlights common challenges learners face, such as confusion over countable and uncountable nouns, omission of articles, and misapplication of "a/an" versus "the." The theoretical perspectives on articles emphasize their role in shaping meaning and guiding listener interpretation within communication. The dual conclusions underscore the significance of mastering articles for effective communication and appreciating their subtle but essential contributions to the structure and clarity of English. This comprehensive analysis offers both linguistic insight and practical guidance for understanding one of the language’s most nuanced grammatical features.